Knowledge Production and Global Integration of Uganda’s Climate Change Research: A Scientometric Perspective - Muneer Ahmad; Undie Felicia Nkatv; Gorrety Maria Juma; Sajid Saleem; Julirine Nakanwagi; Nicholas Kamoga (International Journal of Atmosphere, 2026)
This study provides a comprehensive scientometric analysis of climate change research originating from Uganda and indexed in the Web of Science Core Collection between 1974 and 2025. A total of 1,097 publications were identified, which collectively received 785 Total Local Citation Scores (TLCS) and 40,275 Total Global Citation Scores (TGCS).The temporal analysis reveals exponential growth in research productivity, with over 67% of total publications produced during 2020–2025, indicating accelerated scholarly engagement in recent years. Citation impact peaked during 2015–2019, suggesting consolidation of research visibility and influence. Authorship patterns show concentration among a small group of leading scholars, with the most productive author contributing 49 publications, while citation efficiency varied across contributors. Journal distribution indicates preference for multidisciplinary open-access platforms such as PLOS One and Scientific Reports, alongside specialized outlets in climate adaptation and agricultural systems. Document-type analysis confirms dominance of original research articles (74.75%), reflecting strong empirical orientation, while review papers demonstrate comparatively high citation impact. Institutional analysis highlights Makerere University, contributing 45.9% of total output, as the central research hub. International collaboration is extensive, particularly with the United States, United Kingdom, and regional African partners, significantly enhancing citation performance. Overall, Uganda’s climate change research landscape demonstrates rapid expansion, increasing global integration, and strengthening institutional capacity, positioning the country as an emerging contributor to climate scholarship in Sub-Saharan Africa.
Keywords: Climate change research; Uganda; research productivity and citation impact; scientometric analysis